La utopía de Francisco Marroquín de Gustavo González Villanueva: el Obispo Marroquín como artífice en la fundación de un nuevo pueblo americano - Quesada Mora, Gabriel (2014)
We intend to make an approach to a National Project that began in the sixteenth century with Bishop Francisco Marroquín in Guatemala. We wish to deepen into his comprehensive view of human development: fixed settlements, native-born and European families, college education, religious identity, etc. The configuration of this American Nation contains several elements; its complexity is presented as something new and challenging: the foundation of a different kind of human society that sought to meet the precise needs of the Guatemalan people. Added to this, in this National Project sought a more positive view of the human person is presented.